2017
DOI: 10.5603/kp.a2017.0078
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance and determinants of prompt recruitment collaterals during primary percutaneous coronary intervention

Abstract: A b s t r a c tBackground: Due to ischaemic time delays from the chest pain occurrence in acute ST elevation myocardial infarction (STEMI), prompt recruitment collaterals (PRCCs) to infarct-related artery (IRA) are the major protective structures during this period. Aim:We aimed to investigate the clinical significance and determinants of PRCCs in acute STEMI patients. Methods:A total of 1375 consecutive acute STEMI patients were prospectively enrolled in the study. The patients were divided into two groups, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
1
7
1
Order By: Relevance
“…Failure to recanalize CTO lesion in diabetes was found to have higher residual platelet reactivity (HRPR) which may in turn increase cardiac mortality [18]. In the present study, we found similar result that diabetes mellitus was related to poor prognosis in patients with CTO lesions [19]. Potential mechanisms for collateral developments were arteriogenesis, (i.e., arterialization of capillary bed) and angiogenesis [20].…”
Section: Discussionsupporting
confidence: 79%
“…Failure to recanalize CTO lesion in diabetes was found to have higher residual platelet reactivity (HRPR) which may in turn increase cardiac mortality [18]. In the present study, we found similar result that diabetes mellitus was related to poor prognosis in patients with CTO lesions [19]. Potential mechanisms for collateral developments were arteriogenesis, (i.e., arterialization of capillary bed) and angiogenesis [20].…”
Section: Discussionsupporting
confidence: 79%
“…Sen O et al found out that diabetes was related to higher incidence of inadequate collateral development in acute coronary syndrome. [19] Potential mechanisms for collateral developments were arteriogenesis, (i.e., arterialization of capillary bed) and angiogenesis. [20] However, chronic hyperglycemia induced microvascular rarefaction in myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…the worse clinical profiles may mask mortality benefit of CCC [ 18 ] because CCC patients have more cardiovascular risk factors which were promotive factors for atherosclerosis, [ 17 , 19 ] and in fact their coronary stenosis were heavier as showed in this research. The more serious the coronary stenosis extent, the greater probability of CCC formation because ischemia and hypoxia were strong stimulative factors for CCC formation.…”
Section: Discussionmentioning
confidence: 83%